Implementasi Asas Transparansi Good Corporate Governance pada BUMD di Indonesia - Donal Devi Amdanata; Yusriadi Yusriadi; Noorhayati Mansor; Nurul Nuzilah Lestari (Politeknik Negeri Bengkalis, 2019)
The Government of Indonesia finally issued a Government Regulation (PP) governing Regionally Owned Enterprises (BUMD), namely PP No. 54 of 2017 concerning BUMD. The PP is the government's answer to the debate about BUMD that has occurred so far. The government provides an opportunity for regional governments to optimize the wealth of their respective regions, but because local governments are not allowed to carry out business activities, establishing BUMD is one way that can be done by local governments to increase Regional Original Revenue (PAD). Even so, the government did not prepare regulations that govern BUMD. With PP No. 54, it is hoped that the parties involved with BUMD have guidelines on how to manage and oversee BUMD operations. The purpose of this study was to determine the level of implementation of Good Corporate Governance (GCG) guidelines on BUMD throughout Indonesia in the form of Regional Corporation (Perseroda). In this study, the scope of the research is limited to examining the implementation of the principle of transparency in the General Guidelines for GCG in Indonesia issued by the National Committee on Governance Policy (KNKG) in 2006. One of the main guidelines for the implementation of the transparency principle is that companies must provide information in a timely, adequate, precise, accurate, and comparable and easily accessible to stakeholders under their rights. To obtain this information, the first step taken is to inventory BUMDs in the form of Perseroda in Indonesia. BUMD data obtained through searching facilities from the internet. Based on the searching, 57 BUMDs were obtained that matched the research criteria. Based on this study, only 35% of BUMDs implemented the principle of transparency, 26% only implemented a part of the transparency principle, and the remaining 39% did not apply the principle of transparency.